PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK TEKS NARASI SISWA KELAS IV DI SEKOLAH DASAR - Ayuni, Lia Rista; Aprinawati, Iis; Yusnira, Yusnira; Rizal, Muhammad Syahrul; Ananda, Rizki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this research is the low listening skills of students in class IV. This research aims to improve the listening skills of class IV students at SDN 008 Rumbio. This research is Classroom Action Research (PTK), which was carried out in two cycles and each cycle consisted of two meetings. The subjects in this research were all 22 class IV students. Data collection techniques include observation, documentation and test techniques. Meanwhile, the data analysis technique used is a combination of qualitative data and quantitative data. Based on the results of research that has been carried out over 2 cycles, at meeting 1 of cycle I, there were 6 students who completed the results with a percentage of 27.27% with an overall average of 58.13 and at meeting 2 it increased to 10 students with a percentage of 54.54 % with an overall average of 65.86. Meanwhile, in the second cycle of meeting 1, there were 16 students who completed the meeting with a percentage of 72.72% with an overall average of 77.27 and there was an increase in meeting 2 to 18 students with a percentage of 81.81% with an overall average of 87. 86. Based on the results of this research, it shows that by implementing the snowball throwing learning model, it can improve the listening skills of grade 4 students at SDN 008 Rumbio. .